2004
DOI: 10.1149/1.1777552
|View full text |Cite
|
Sign up to set email alerts
|

Superfilling Evolution in Cu Electrodeposition

Abstract: Interesting phenomena were observed during an investigation on the accelerating effects of 3-mercapto-1-propane sulfonic acid ͑MPSA͒, i.e., different aging times of MPSA result in different filling profiles. When MPSA was added to the electrolyte immediately before electrodeposition, subconformal deposits appeared, whereas MPSA aged over 12 h enabled superfilling. From UV-visible analysis, over 99% MPSA was converted to bis͑3-sulfopropyl͒disulfide ͑SPS͒ within 12 h through the reaction with Cu 2ϩ , which means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
92
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 15 publications
0
92
0
1
Order By: Relevance
“…This means that 2 equivalents of MPS was more effective than 1 equivalent of SPS in accelerating Cu reduction on the flat electrode, as reported by Tan et al and Moffat et al who observed the stronger acceleration effect of MPS than SPS using chronoamperometry experiments. 46,47 Despite the superfilling-incapability of MPS, its electrochemical acceleration effect, as shown in Figure 2 and the literature, 22,23,[44][45][46] might lead to significant error in the results of conventional MLAT-CVS analysis since the electrochemical responses of SPS and MPS are not distinguishable in the conventional MLAT-CVS. (Note that conventional MLAT-CVS provides only a stripping charge value, regardless of where the increased stripping charges originate-from either MPS or SPS).…”
Section: ) Concentration Of Total Accelerating Compounds (C T )mentioning
confidence: 99%
See 1 more Smart Citation
“…This means that 2 equivalents of MPS was more effective than 1 equivalent of SPS in accelerating Cu reduction on the flat electrode, as reported by Tan et al and Moffat et al who observed the stronger acceleration effect of MPS than SPS using chronoamperometry experiments. 46,47 Despite the superfilling-incapability of MPS, its electrochemical acceleration effect, as shown in Figure 2 and the literature, 22,23,[44][45][46] might lead to significant error in the results of conventional MLAT-CVS analysis since the electrochemical responses of SPS and MPS are not distinguishable in the conventional MLAT-CVS. (Note that conventional MLAT-CVS provides only a stripping charge value, regardless of where the increased stripping charges originate-from either MPS or SPS).…”
Section: ) Concentration Of Total Accelerating Compounds (C T )mentioning
confidence: 99%
“…Similar results were reported by Kim et al showing that MPS itself is unable to induce bottom-up filling, whereas its dimerized form, SPS, enabled superfilling. 22 One notable point is the adverse effect of MPS on the filling capability. Figures 3a and 3d show that in the absence of MPS in the plating solution, an SPS concentration within the range of 25-50 μM is sufficient to induce superfilling.…”
Section: ) Concentration Of Total Accelerating Compounds (C T )mentioning
confidence: 99%
“…Locally crowded accelerator in the trench enhances the deposition rate and makes the superfilling. [8][9][10] Some organic accelerators, for example, 3-mercapto-1-propane-sulfonic acid ͑MPSA͒, 8,[11][12][13] bis͑3-sulfopropyl͒ disulfide, disodium salt ͑SPS͒, 9,10,12,14,15 and 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid ͑DPS͒ 16 are known as superfilling-capable accelerators. In Ag electroplating, there has been little research about accelerators.…”
mentioning
confidence: 99%
“…12 The electrochemical deposition on thiolate pre-patterned surface has been reported several times for the electrodeposition of metals, including nikel electrodeposited on gold, 13,14 gold/ silver electrodeposited on gold, 15,16 and Cu electrodeposited on printed SAM. 17 Recently, Seo et al reported nanoshaving combined with silver electrodeposition on Au(111). 18 Here, we investigate for the first time how, by confining the growth of CdS thin films by combined ECALE, CdS nanoclusters grow and self-organizes into an ordered pattern organized at nanoscale.…”
mentioning
confidence: 99%